OPTIMIZATION OF THE HAJJ AND UMRAH MANAGEMENT SYSTEM: EFFICIENCY AND EFFECTIVENESS OF PILGRIM SERVICES - Hafsah US; Loso Judijanto; Abdul Wahab Syakhrani (CV. Adiba Aisha Amira, 2024)
The organization of Hajj and Umrah is one of the important responsibilities of the Indonesian government in serving Muslims. With the number of pilgrims increasing every year, optimizing the management system is key in ensuring excellent service quality. The research method used is literature. The results show that the implementation of integrated information technology, standardization of operational procedures, increased officer competence, and a pilgrim-focused service approach are key factors in optimizing the management system. Efficiency is achieved through automation of administrative processes, better data management, and more effective inter-agency coordination. Meanwhile, service effectiveness is improved through the provision of comprehensive information, quality ritual guidance, adequate health services, and a responsive complaint handling system. Thus, this study emphasizes the importance of continuous evaluation and improvement in the Hajj and Umrah management system to face dynamic challenges. Recommendations for future research include comparative studies with other countries and analysis of the long-term impact of system optimization on pilgrim satisfaction and Indonesia's image internationally.